A classroom experiment with bank equity, deposit insurance, and bailouts. Issue 4 (1st October 2016) - Hazlett, Denise
ABSTRACT: In this classroom experiment, students see how low bank equity requirements can interact with deposit insurance to encourage excessive risk-taking. The experiment fills a niche Admati and Hellwig (2013 ) have noted: citizens in a democracy must understand why bank owners argue for low equity requirements and why society as a whole is better off with higher requirements. Instructors can run the experiment in principles of economics courses to introduce the topics of banking and financial crisis, or in advanced courses to promote discussion of financial reform. It takes about 45 minutes to run and debrief, and requires no computerization.